A CASE REPORT OF TOXOCARA CATI INFECTION IN A DOMESTIC SHORTHAIR CAT FROM UDUMALPET, TAMIL NADU: CLINICAL AND ZOONOTIC IMPLICATIONS - T. Rama; M. Palanivelrajan; N. Rani; V. Naveenkumar; D. Chandrasekaran (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Toxocariasis is a parasitic zoonotic disease of public health significance, especially in children, causing visceral and ocular larva migrans. While Toxocara canis in dogs is well-documented, T. cati in cats also poses a notable risk but remains underreported, underscoring the need for greater attention to feline sources.This paper reports a case of T. cati infection in a domestic cat diagnosed at the Veterinary Clinical Complex, Veterinary College and Research Institute, Udumalpet, Tamil Nadu. A 4-month- old female domestic shorthair kitten was presented with a history of inappetence and vomiting with white-coloured worms expelled in the vomitus for the past two days. Clinical examination revealed that the animal was moderately dehydrated and visible mucous membranes were slightly pale. The faecal examination by direct smear and flotation did not reveal the presence of ova of parasites. Based on the morphological features of the adult worms recovered from the vomitus, it was identified T. cati. This report is made to highlight the epidemiological and zoonotic significance of T. cati, besides to emphasize the importance of deworming and personal hygiene, to prevent transmission of parasitic diseases from animal to man.